Aqueous mq silicone film-forming resin, process for its preparation and use in make-up
Patent Information
- Application Number
- CN202611504870.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-24
- Publication Date
- 2026-10-30
AI Technical Summary
又如CN101244018A公开了含水硅MQ树脂增强的有机硅弹性体乳液用于个人护理配方,但其重点在于弹性体膜形成,仍难充分解决提高分散稳定性时亲水界面组分增加导致耐水性下降,以及强化疏水MQ树脂连续相时分散稳定性和肤感舒适性下降的问题
1.本发明通过三甲基硅烷氧基硅酸酯与PEG-12聚二甲基硅氧烷的界面预复合,使PEG-12聚二甲基硅氧烷在乳胶粒体系中发挥界面稳定作用,从而在提高水性分散稳定性的同时减少游离亲水组分对疏水膜层的削弱,有利于改善彩妆体系中的耐水持妆表现。
Smart Images

Figure CN122997982A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of waterborne organosilicon film-forming materials, specifically to a waterborne MQ organosilicon film-forming resin, its preparation method, and its application in color cosmetics. Background Technology
[0002] Makeup products, particularly foundation, eye makeup, lip makeup, and waterproof / long-lasting makeup systems, typically require the formation of a continuous, uniform film with appropriate flexibility on the skin or makeup base surface to improve adhesion, coverage, water resistance, sweat resistance, and abrasion resistance. Simultaneously, the formulation must maintain dispersion stability, spreadability, and user comfort. MQ silicone resin, due to its silicon-oxygen network structure and hydrophobic silanyl structure, is frequently used as a film-forming component in makeup to improve film integrity and water resistance. Polyether-modified siloxanes can improve the emulsification and interfacial stability of the silicone phase in aqueous systems. Existing publicly available technologies have already utilized trimethylsiloxysilicate, MQ silicone resin, and polyether-modified siloxanes in makeup or personal care film-forming systems, indicating a clear application basis for these materials.
[0003] Existing aqueous or emulsion-based silicone film-forming systems still face challenges in achieving formulation balance. For example, Chinese patent CN109021574A discloses an aqueous methyl MQ silicone resin emulsion and its preparation method, emphasizing its use in cosmetics, textiles, hair care products, and waterproofing. However, this type of disclosure focuses more on the general dispersion and film-forming applications of methyl MQ silicone resin emulsions, without specifically addressing the synergistic relationship between trimethylsiloxane and PEG-12 polydimethylsiloxane in interfacial precomposite, latex particle size control, low volatility control, and makeup comfort. Similarly, CN101244018A discloses a silicone elastomer emulsion reinforced with hydrophilic silicone MQ resin for personal care formulations, but its focus is on elastomer film formation. It still struggles to fully address the issues of decreased water resistance due to increased hydrophilic interfacial components when improving dispersion stability, and decreased dispersion stability and skin comfort when reinforcing the hydrophobic MQ resin continuous phase. Summary of the Invention
[0004] The purpose of this invention is to provide an aqueous MQ organosilicon film-forming resin, its preparation method, and its application in color cosmetics, thereby solving the current pain points of difficulty in achieving both dispersion stability and water resistance, and difficulty in unifying film structure integrity and skin comfort.
[0005] This invention achieves a ratio matching between the hydrophobic film-forming network of trimethylsiloxysilicate and the interfacial stabilizing effect of PEG-12 polydimethylsiloxane, and combines it with interfacial pre-composite, phase inversion emulsification and low volatility treatment to control the weakening of water resistance by hydrophilic interfacial components, while reducing the risk of dispersion instability and film stiffness caused by the enrichment of hydrophobic resin.
[0006] To achieve the above objectives, the present invention provides the following technical solution: An aqueous MQ silicone film-forming resin, based on a final total mass of 100 wt%, comprises the following components: 30.00–55.00 wt% trimethylsiloxysilicate; 2.00–12.00 wt% of PEG-12 polydimethylsiloxane; 40.00–68.00 wt% deionized water; 0–8.00 wt% ethanol; 0–0.50 wt% pH adjusting component; Preservation components: 0–1.50 wt%; The content of each component is selected such that the total content of the aqueous MQ organosilicon film-forming resin is 100 wt%. The trimethylsiloxane silicate has an M / Q molar ratio of 0.55–1.10 and a silanol content of 0.30–4.50 wt%. The trimethylsiloxane and the PEG-12 polydimethylsiloxane are pre-composite, phase-conversion emulsification and aging stabilization to form a trimethylsiloxane-PEG-12 polydimethylsiloxane interface-modified latex particle dispersion system.
[0007] Furthermore, the D50 of the trimethylsiloxysilicate-PEG-12 polydimethylsiloxane interface-modified latex particles is 80–500 nm, the PDI is 0.08–0.35, and the pH value of the aqueous MQ organosilicon film-forming resin is 5.50–7.50. The D50 and PDI are both arithmetic mean values obtained from three parallel measurements using the dynamic light scattering method.
[0008] Furthermore, the trimethylsiloxysilicate-PEG-12 polydimethylsiloxane interface-modified latex particles are prepared through the following steps: A1. Steps for providing trimethylsiloxysilicate: providing trimethylsiloxysilicate having an M / Q molar ratio of 0.55–1.10 and a silanol content of 0.30–4.50 wt%; A2. Pre-dispersion step: The trimethylsiloxysilicate is mixed with ethanol and / or deionized water and pre-dispersion is performed to obtain a trimethylsiloxysilicate pre-dispersion solution; A3. Interface pre-composite step: PEG-12 polydimethylsiloxane is added to the trimethylsiloxane pre-dispersion to allow the PEG-12 polydimethylsiloxane to undergo interface pre-composite with the trimethylsiloxane to obtain an interface pre-composite system; A4. Reverse emulsification step: Under shear conditions, deionized water is added to the interfacial precomposite system to cause reverse emulsification of the system, forming a trimethylsiloxysilicate-PEG-12 polydimethylsiloxane interfacial modified latex particle dispersion. A5. Aging stabilization step: The trimethylsiloxysilicate-PEG-12 polydimethylsiloxane interface-modified latex particle dispersion is subjected to aging treatment; A6. Filtration and granulation steps: Filter the aged dispersion to obtain a trimethylsiloxysilicate-PEG-12 polydimethylsiloxane interface-modified latex particle dispersion system. A7. Preservation and pH Post-treatment Steps: The dispersion system obtained in step A6 is subjected to preservation component addition and pH adjustment treatment to obtain a preservation-type waterborne MQ organosilicon film-forming resin.
[0009] Unless otherwise stated, all component contents in this instruction manual are by mass percentage. The final total mass refers to the total mass of the product after the preservation components have been added, pH adjusted, and filtered. The pH adjustment components refer to the non-aqueous components remaining in the final product from the hydrochloric acid and / or sodium hydroxide used to adjust the pH of the system. Water introduced by acid and alkaline aqueous solutions is counted as deionized water.
[0010] In this article, the M / Q molar ratio refers to the molar ratio of trimethylsiloxy M units to SiO4 / 2Q units; the silanol content is expressed as the mass fraction of silanol groups in trimethylsiloxane silicate. "Interfacial pre-composite" refers to adding PEG-12 polydimethylsiloxane to a trimethylsiloxane pre-dispersion and heating and stirring it before reverse emulsification to form an interfacial pre-composite system for subsequent reverse emulsification; "interfacial modified latex particles" refers to latex particles containing trimethylsiloxane silicate and PEG-12 polydimethylsiloxane formed through interfacial pre-composite, reverse emulsification, and aging stabilization, which does not necessarily indicate the formation of covalent bonds, a complete shell, or a surface monolayer.
[0011] The PEG-12 polydimethylsiloxane retention rate described in this article is used to characterize its retention in the latex particle-enriched phase; the total amounts of octamethylcyclotetrasiloxane, decamethylcyclopentasiloxane, and dodecylcyclohexasiloxane, unless otherwise stated, are expressed as the mass of trimethylsiloxysilicate solids. Watercolor-containing cosmetic bases refer to cosmetic bases containing an aqueous phase with a measurable pH value, where the pH value is the pH of that aqueous phase.
[0012] Furthermore, in step A1, the trimethylsiloxysilicate is provided in the following manner: Tetraethyl silicate, ethanol, deionized water and hydrochloric acid aqueous solution were mixed and hydrolyzed to obtain Q unit hydrolysis condensate; Hexamethyldisiloxane was added to the hydrolysis condensate of the Q unit and condensed to obtain a trimethylsiloxysilicate reaction solution. The pH of the trimethylsiloxysilicate reaction solution was adjusted to 6.00–7.50 using sodium hydroxide. The pH-adjusted system was subjected to phase separation, water washing, and vacuum devolatilization to obtain trimethylsilyloxysilicate. The resulting trimethylsiloxane silicate has an M / Q molar ratio of 0.55–1.10, a silanol content of 0.30–4.50 wt%, and a residual ethanol content of 0.05–5.00 wt%.
[0013] Further, in step A1, the trimethylsiloxysilicate undergoes a low-volatility pretreatment before proceeding to step A2, the low-volatility pretreatment including: Trimethylsiloxane silicate was dispersed in a mixture of ethanol and deionized water and stirred. After standing and separating into layers or by centrifugation, the silicate phase is taken; The silicate phase was subjected to vacuum devolatilization to obtain low-volatility trimethylsiloxy silicate; The total amount of octamethylcyclotetrasiloxane, decamethylcyclopentasiloxane and dodecylcyclohexasiloxane in the low-volatility trimethylsiloxysilicate is 0.02–0.50 wt%.
[0014] Furthermore, steps A2 to A7 include the following conditions: In step A2, the trimethylsiloxysilicate is mixed with at least one of ethanol and deionized water and heated and stirred to obtain the trimethylsiloxysilicate predispersant. In step A3, PEG-12 polydimethylsiloxane is added to the trimethylsiloxysilicate predispersant, and the mixture is heated, stirred, and the pH is adjusted to obtain the interfacial precomposite system. In step A4, deionized water is added to the interfacial precomposite system under shear conditions to cause the system to undergo reverse emulsification, thereby obtaining the trimethylsiloxysilicate-PEG-12 polydimethylsiloxane interfacial modified latex particle dispersion. In step A5, the trimethylsiloxysilicate-PEG-12 polydimethylsiloxane interface-modified latex particle dispersion is subjected to aging treatment. In step A6, the aged dispersion is filtered to obtain the trimethylsiloxysilicate-PEG-12 polydimethylsiloxane interface-modified latex particle dispersion system. In step A7, the preservation component is added to the dispersion system obtained in step A6 and the pH value is adjusted. After stirring and filtration, the preservation-type waterborne MQ organosilicon film-forming resin is obtained. At the end of step A5, the retention rate of PEG-12 polydimethylsiloxane in the trimethylsiloxysilicate-PEG-12 polydimethylsiloxane interface-modified latex particles is 60.00–95.00%, and the D50 of the trimethylsiloxysilicate-PEG-12 polydimethylsiloxane interface-modified latex particles is 80–500 nm, and the PDI is 0.08–0.35. The preservation-type aqueous MQ organosilicon film-forming resin has a solid content of 32.00–58.00 wt% and a pH value of 5.50–7.50.
[0015] Furthermore, steps A2 to A7 satisfy the following process parameters: In step A2, 100 parts by weight of the trimethylsiloxysilicate is mixed with 8–30 parts by weight of ethanol and 0–10 parts by weight of deionized water, and stirred at 45–70°C for 0.50–2.00 h. In step A3, the amount of PEG-12 polydimethylsiloxane added is 4–20 parts by weight, the mixture is stirred at 50–75°C for 0.50–3.00 h, and the pH of the system is adjusted to 5.50–7.50. In step A4, the shearing conditions are 1500–8000 rpm, the amount of deionized water added is 80–180 parts by mass, and the addition time is 0.50–3.00 h; In step A5, the aging treatment temperature is 30–60℃ and the time is 1.00–6.00h; In step A7, 0.20–1.50 parts by mass of the preservation component are added to 100 parts by mass of the dispersion system obtained in step A6, and the pH value of the system is adjusted to 5.50–7.50. The pH-adjusted system is stirred at 20–40°C for 0.50–2.00 h and filtered to obtain the preservation-type waterborne MQ organosilicon film-forming resin. The amounts of ethanol, deionized water, PEG-12 polydimethylsiloxane, pH adjustment component and preservation component added in steps A2 to A7 are coordinated to ensure that the obtained preservation-type waterborne MQ organosilicon film-forming resin meets the content range of each component.
[0016] Furthermore, the total amount of octamethylcyclotetrasiloxane, decamethylcyclopentasiloxane and dodecylcyclohexasiloxane in the aqueous MQ organosilicon film-forming resin is 0.02–0.30 wt%.
[0017] Furthermore, the apparent viscosity of the aqueous MQ organosilicon film-forming resin is 200–5000 mPa·s, and the D50 change rate of the trimethylsiloxysilicate-PEG-12 polydimethylsiloxane interface-modified latex particles after storage at 45°C for 8 weeks is 0.50–15.00%.
[0018] This invention employs a design that modifies latex particles using the interface of trimethylsiloxysilicate and PEG-12 polydimethylsiloxane, primarily to achieve a synergistic balance between dispersion stability and water-resistant film formation. Existing technologies typically enhance the hydrophilic polyether interface to improve waterborne dispersion stability; however, excessive hydrophilic components weaken the water retention capacity of the hydrophobic film. Conversely, improving water resistance often relies on increased contributions from hydrophobic MQ silicone resin, easily leading to unstable latex particle dispersion, uneven coating, and a hard feel. This invention, through matching the content of trimethylsiloxysilicate, the M / Q molar ratio, the silanol content, and the PEG-12 polydimethylsiloxane content, and by ensuring that PEG-12 polydimethylsiloxane plays an interfacial stabilizing role in the latex particle system, reduces the adverse effects of these two conventional methods, achieving a balance between dispersion, film formation, water resistance, and comfortable use.
[0019] This invention also discloses a method for preparing an aqueous MQ organosilicon film-forming resin, comprising the following steps: S1. Provides trimethylsiloxysilicate, PEG-12 polydimethylsiloxane, deionized water and ethanol; S2. The trimethylsiloxysilicate is mixed with the ethanol and / or deionized water and heated and stirred to obtain a trimethylsiloxysilicate predispersant; S3. Add the PEG-12 polydimethylsiloxane to the trimethylsiloxysilicate predispersant and heat and stir to obtain an interfacial precomposite system; S4. Under shear conditions, the deionized water is added to the interfacial precomposite system to form a trimethylsiloxysilicate-PEG-12 polydimethylsiloxane interfacial modified latex particle dispersion; S5. The trimethylsiloxysilicate-PEG-12 polydimethylsiloxane interface-modified latex particle dispersion obtained in step S4 is subjected to aging treatment, and the pH value is adjusted to 5.50–7.50. After filtration, water-based MQ organosilicon film-forming resin is obtained.
[0020] Furthermore, the trimethylsiloxysilicate provided in step S1 is a trimethylsiloxysilicate that has undergone low-volatility pretreatment, and the trimethylsiloxysilicate that has undergone low-volatility pretreatment is obtained according to the above-described low-volatility pretreatment method.
[0021] Further, 0.20–1.50 parts by weight of a preservation component are added to 100 parts by weight of the aqueous MQ silicone film-forming resin obtained in step S5. The preservation component is selected from one or more of phenoxyethanol, 1,2-hexanediol and ethylhexylglycerol.
[0022] Furthermore, steps S1 to S5 are repeated for 3 batches, and the solid content of the obtained waterborne MQ organosilicon film-forming resin has an inter-batch coefficient of variation of 0.50–5.00%, and the D50 of the trimethylsiloxysilicate-PEG-12 polydimethylsiloxane interface modified latex particles has an inter-batch coefficient of variation of 0.50–10.00%.
[0023] Furthermore, step S5 is followed by step S6: the aqueous MQ silicone film-forming resin obtained in step S5 is added to the watercolor-containing makeup matrix in an amount of 3.00–35.00 wt% of the total mass of the added system, wherein the pH of the makeup matrix is 5.50–8.00.
[0024] This invention also discloses the application of a water-based MQ silicone film-forming resin in color cosmetics. The water-based MQ silicone film-forming resin is added to a water-containing cosmetic matrix to improve one or more of the following properties of the color cosmetic product: film-forming properties, makeup-holding properties, water resistance, abrasion resistance, and skin comfort. The water-based MQ silicone film-forming resin has a content of 3.00–35.00 wt% in the system after addition, and the pH value of the color cosmetic matrix is 5.50–8.00.
[0025] Further, 100 parts by mass of trimethylsiloxysilicate are dispersed in a mixture of 20–80 parts by mass of ethanol and 10–60 parts by mass of deionized water. After stirring at 25–55°C for 0.50–3.00 h, the mixture is allowed to stand and separate into layers. The silicate phase is then collected. The silicate phase is subjected to vacuum desorption at 60–95°C and 0.001–0.020 MPa for 2.00–10.00 h to obtain low-volatility trimethylsiloxysilicate. This low-volatility trimethylsiloxysilicate is used as the trimethylsiloxysilicate in the pre-dispersion step, wherein the total amount of octamethylcyclotetrasiloxane, decamethylcyclopentasiloxane, and dodecylcyclohexasiloxane is 0.02–0.50 wt%.
[0026] Further, 100 parts by weight of trimethylsiloxysilicate was mixed with 8–30 parts by weight of ethanol and 0–10 parts by weight of deionized water, and stirred at 45–70°C for 0.50–2.00 h to obtain a trimethylsiloxysilicate predispersant; 4–20 parts by weight of PEG-12 polydimethylsiloxane were added to the trimethylsiloxysilicate predispersant, and stirred at 50–75°C for 0.50–3.00 h, and the pH of the system was adjusted to 5.5 using one or both of hydrochloric acid aqueous solution and sodium hydroxide aqueous solution. 0–7.50, to obtain an interfacial pre-composite system; under shear conditions of 1500–8000 rpm, 80–180 parts by mass of deionized water were added to the interfacial pre-composite system within 0.50–3.00 h to obtain a trimethylsiloxysilicate-PEG-12 polydimethylsiloxane interfacial modified latex particle dispersion; the latex particle dispersion was aged at 30–60 °C for 1.00–6.00 h and filtered to obtain a trimethylsiloxysilicate-PEG-12 polydimethylsiloxane interfacial modified latex particle dispersion system.
[0027] Further, 0.20–1.50 parts by weight of a preservation component, selected from one or more of phenoxyethanol, 1,2-hexanediol, and ethylhexylglycerol, are added to 100 parts by weight of the trimethylsiloxysilicate-PEG-12 polydimethylsiloxane interface-modified latex particle dispersion system. The pH of the system is adjusted to 5.50–7.50 using one or both of hydrochloric acid aqueous solution and sodium hydroxide aqueous solution. The mixture is stirred at 20–40°C for 0.50–2.00 h and filtered to obtain a preservation-type aqueous MQ organosilicon film-forming resin. Ethanol, deionized water, and PEG-12... The amounts of polydimethylsiloxane, pH adjusting component, and preservation component are added in a coordinated manner. The resulting preservation-type waterborne MQ organosilicon film-forming resin, based on a final total mass of 100wt%, contains trimethylsiloxysilicate, PEG-12 polydimethylsiloxane, deionized water, ethanol, pH adjusting component, and preservation component at contents of 30.00–55.00wt%, 2.00–12.00wt%, 40.00–68.00wt%, 0–8.00wt%, 0–0.50wt%, and 0–1.50wt%, respectively, and the sum of the contents of all components is 100wt%.
[0028] This invention employs a combined preparation and application design involving pre-dispersion, interfacial pre-compositing, phase-conversion emulsification, aging treatment, and application in a cosmetic matrix. It is primarily used to achieve, fix, or amplify the aforementioned synergistic effects. Conventional direct emulsification methods easily cause PEG-12 polydimethylsiloxane to remain free in the aqueous phase or distribute unevenly, making it difficult to simultaneously maintain dispersion stability and hydrophobic film formation. Simply increasing shear strength may also lead to a wider particle size distribution and unstable latex particle interfacial structure. This invention first forms a trimethylsiloxysilicate pre-dispersion, then performs interfacial pre-compositing with PEG-12 polydimethylsiloxane, followed by phase-conversion emulsification under shear conditions and aging stabilization. This makes it easier to fix the stable interfacial state and particle size of the latex particles during preparation. When added to a watercolor-containing cosmetic matrix at a defined content, it ensures that the film-forming durability and user comfort continue to perform well in the target application environment.
[0029] Trimethylsiloxane primarily contributes to hydrophobic film formation, film structural integrity, and water retention. While its presence alone or in excessive proportions promotes the formation of more continuous films, it can weaken aqueous dispersion stability and skin comfort due to the enrichment of hydrophobic phases, enhanced interfacial constraints, and increased film rigidity. PEG-12 polydimethylsiloxane mainly improves the interfacial wetting of latex particles and aqueous dispersion stability. While its presence alone or in excessive proportions facilitates emulsification and spreading, it may reduce water retention and film transfer resistance due to the increased contribution of hydrophilic polyether interfaces. This invention achieves a balance by matching the content ratio, M / Q molar ratio, silanol content, interfacial pre-composite sequence, and phase-conversion emulsification conditions, allowing PEG-12 polydimethylsiloxane to concentrate its interfacial stabilizing effect while retaining the hydrophobic film-forming contribution of trimethylsiloxane, ultimately resolving these inherently contradictory properties.
[0030] Beneficial technical effects 1. This invention pre-compositely combines trimethylsiloxysilicate with PEG-12 polydimethylsiloxane at the interface, enabling PEG-12 polydimethylsiloxane to play an interfacial stabilizing role in the latex particle system. This improves the stability of water-based dispersion while reducing the weakening of the hydrophobic film layer by free hydrophilic components, which is beneficial to improving the water resistance and makeup longevity performance in color cosmetic systems.
[0031] 2. This invention limits the M / Q molar ratio and silanol content of trimethylsiloxysilicate to achieve an appropriate balance between the contribution of the MQ resin network and the flexibility of the film layer. This avoids incomplete film formation due to an overly loose film structure and reduces the risk of skin discomfort caused by an overly hard film layer, thus making it suitable for everyday makeup application scenarios.
[0032] 3. The present invention adopts a process sequence of pre-dispersion, interfacial pre-composite, phase-conversion emulsification and aging stabilization, which gives the hydrophobic MQ resin phase a more sufficient basis for interfacial regulation before entering the aqueous system, which helps to form a latex particle dispersion system with controlled particle size distribution, low PDI and controllable particle size change after storage.
[0033] 4. The present invention further incorporates low-volatility pretreatment and storage and pH posttreatment, which can reduce the residual risk of octamethylcyclotetrasiloxane, decamethylcyclopentasiloxane and dodecylcyclohexasiloxane, and make the pH of the finished product suitable for watercolor-containing cosmetic bases, which is beneficial to improving product formulation compatibility, storage stability and practical application operability. Attached Figure Description
[0034] Figure 1 The image shows the particle size distribution of DLS particles in Example 1, Comparative Example 7, and Comparative Example 11.
[0035] Figure 2 The cumulative particle size distribution of DLS latex particles in Example 1, Comparative Example 7, and Comparative Example 11 is shown.
[0036] Figure 3 This is a comparison chart of the average D50 values of the interface-modified latex particles in Example 1, Comparative Example 7, and Comparative Example 11.
[0037] Figure 4 This is a comparison chart of the mass retention rates after water immersion for Example 1, Comparative Example 5, and Comparative Example 6.
[0038] Figure 5 This is a comparison chart of frictional mass loss for Example 1, Comparative Example 5, and Comparative Example 6.
[0039] Figure 6 The graph shows a comparison of the coefficients of kinetic friction for Example 1, Comparative Example 5, and Comparative Example 6.
[0040] Figure 7 The graph shows the changes in mass retention and frictional mass loss of waterborne MQ silicone film-forming resin samples with different PEG-12 polydimethylsiloxane contents after water immersion.
[0041] Figure 8 This is a comparison of macroscopic optical photographs of the final product of Example 1 and the final product of Comparative Example 11; wherein, Figure 8 Figure a in the image is a macroscopic optical photograph of the final product of Example 1, an aqueous MQ organosilicon film-forming resin latex particle dispersion. Figure 8 Figure b in the figure is a macroscopic optical photograph of the final product of Comparative Example 11, which was not subjected to interfacial precomposite treatment: an aqueous MQ organosilicon film-forming resin latex particle dispersion.
[0042] Figure 9The images show the scanning electron microscope (SEM) morphology of the final product of Example 1 and the final product of Comparative Example 11; wherein, Figure 9 Figure a in the image is a low-magnification scanning electron microscope image of the dry deposition region of the final product in Example 1; Figure 9 Figure b in the figure is a low-magnification scanning electron microscope image of the dry deposition area of the final product in Comparative Example 11; Figure 9 Figure c in the image is a medium-magnification scanning electron microscope image of the localized accumulation state of latex particles in the final product of Example 1. Figure 9 Image d in the image is a medium-magnification scanning electron microscope image of the localized accumulation state of latex particles in the final product of Comparative Example 11. Figure 9 Figure e in the image is a high-magnification scanning electron microscope image showing the local morphology and dry-state stacking details of the final product nano-latex particles from Example 1. Detailed Implementation
[0043] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings.
[0044] In the following examples, the "parts by mass" mentioned in the pretreatment, predispersion, interfacial precomposition, and phase inversion emulsification steps of low-volatility trimethylsiloxysilicate are used to indicate the process feed ratio during the preparation of the latex particle mother liquor; the finished product composition mentioned at the beginning of each example is based on the total mass of the final product. The latex particle mother liquor is mixed with the preservation components, pH adjusted, and formulated according to the corresponding finished product composition to obtain the final product, with deionized water as a supplementary component to make the total of all components reach 100 wt%.
[0045] Example 1 S1: Preparation Target, Scale, and Raw Material State. This embodiment prepares 1000g of aqueous MQ organosilicon film-forming resin, in the form of an aqueous latex particle dispersion. The finished product, based on a final total mass of 100wt%, contains 30.00wt% trimethylsiloxysilicate, 2.00wt% PEG-12 polydimethylsiloxane, 67.80wt% deionized water, 0.00wt% ethanol, 0.00wt% pH adjustment component, and 0.20wt% preservation component. Trimethylsiloxysilicate is commercially available or prepared according to the steps of this embodiment, with a purity ≥98.0% on a solids basis, an M / Q molar ratio of 0.55, and a silanol content of 4.50wt%. PEG-12 polydimethylsiloxane is a commercially available cosmetic-grade raw material with an active ingredient content ≥98.0% and a moisture content ≤1.0%. The conductivity of deionized water is ≤5μS / cm. The preservation component is phenoxyethanol with a purity ≥99.0%.
[0046] S2: Providing trimethylsilyloxysilicate and low-volatility pretreatment: Tetraethyl silicate, ethanol, deionized water, and 0.10 mol / L hydrochloric acid aqueous solution were added to a reactor equipped with mechanical stirring, a thermometer, and a condenser. Hydrolysis was carried out at 25 °C and 300 rpm for 1.00 h to obtain the Q unit hydrolysis condensate. Hexamethyldisiloxane was then added, and condensation was carried out at 45 °C and 300 rpm for 2.00 h. The pH of the system was adjusted to 6.00 using 0.10 mol / L sodium hydroxide aqueous solution. After phase separation, water washing, and vacuum devolatilization, trimethylsilyloxysilicate was obtained. Subsequently, 100 parts by mass of trimethylsilyloxysilicate were taken, and 20 parts by mass of ethanol and 10 parts by mass of deionized water were added. The mixture was stirred at 25 °C and 300 rpm for 0.50 h. After standing and layering, the silicate phase was collected and devolatilized under reduced pressure at 60 °C and 0.020 MPa for 2.00 h to obtain low-volatility trimethylsilyloxysilicate. Gas chromatography analysis revealed that the total amount of octamethylcyclotetrasiloxane, decamethylcyclopentasiloxane, and dodecylcyclohexasiloxane was 0.02 wt%.
[0047] S3: Pre-dispersion and interfacial pre-composite: 100 parts by mass of low-volatility trimethylsiloxysilicate was added to 8 parts by mass of ethanol and 0 parts by mass of deionized water. The mixture was stirred at 500 rpm for 0.50 h at 45 °C to obtain a trimethylsiloxysilicate pre-dispersion. 4 parts by mass of PEG-12 polydimethylsiloxane were added to this pre-dispersion, and the mixture was stirred at 500 rpm for 0.50 h at 50 °C. The pH of the system was 5.50, thus obtaining the interfacial pre-composite system.
[0048] S4: Conversely, emulsification, aging stabilization, and filtration granulation are performed. Under a shear condition of 1500 rpm, 80 parts by mass of deionized water are continuously added to the interfacial precomposite system over 0.50 h to form a trimethylsiloxysilicate-PEG-12 polydimethylsiloxane interfacial modified latex particle dispersion. After the water addition is complete, the dispersion is aged at 30°C and 300 rpm for 1.00 h, then pre-filtered through a 100-mesh filter and filtered through a 0.80 μm filter membrane to obtain the trimethylsiloxysilicate-PEG-12 polydimethylsiloxane interfacial modified latex particle dispersion system. This dispersion system is used as the latex particle mother liquor and is prepared according to the finished product composition described in S1, wherein the preserved component is phenoxyethanol. After stirring and filtration, 1000 g of the aqueous MQ organosilicon film-forming resin of this embodiment is obtained.
[0049] S5: Quality Inspection Methods and Results. The sample from this embodiment was diluted 100 times with deionized water and subjected to dynamic light scattering testing at 25°C for 2 minutes. The test was repeated three times, with a D50 of 80 nm and a PDI of 0.08. The pH value was measured to be 5.50 using a pH meter calibrated with pH 4.00, pH 6.86, and pH 9.18 buffer solutions. The solid content was determined to be 32.00 wt% by drying at 105°C to constant weight. The apparent viscosity was measured to be 200 mPa·s using a rotational viscometer at 25°C and 20 rpm. After centrifugation, the PEG-12 polydimethylsiloxane content in the supernatant was determined, and the retention rate of PEG-12 polydimethylsiloxane in the latex particles was calculated to be 60.00%. After storage at 45°C for 8 weeks, the D50 change rate was 0.50%. Three batches were prepared repeatedly, with an inter-batch coefficient of variation of 0.50% for both solid content and D50.
[0050] S6: Features and Application Scenarios of this Embodiment. This embodiment adopts a relatively conservative low-ratio scheme. Trimethylsiloxane and PEG-12 polydimethylsiloxane are in the low-value range, while the deionized water content is in the high-value range. The pre-dispersion, interfacial pre-composite, shear emulsification, and aging stability conditions are all relatively mild, making it suitable for foundation, primer, and everyday light makeup systems that require high water-based dispersion stability, low-viscosity coating, and a light, thin makeup feel. Adding the water-based MQ silicone film-forming resin of this embodiment at 3.00 wt% of the total mass of the added system to a water-containing makeup matrix with a pH of 5.50, stirring at 600 rpm for 20 minutes, yields a low-load water-based film-forming makeup sample.
[0051] Example 2 The water-based MQ organosilicon film-forming resin of this embodiment was prepared according to a 1000g finished product scale. The finished product, based on a final total mass of 100wt%, contains 55.00wt% trimethylsiloxysilicate, 2.00wt% PEG-12 polydimethylsiloxane, 40.00wt% deionized water, 1.00wt% ethanol, 0.50wt% pH adjusting component, and 1.50wt% preservation component. The M / Q molar ratio of trimethylsiloxysilicate is 1.10, and the silanol content is 0.30wt%. The pH adjusting component is the non-aqueous component remaining in the finished product from the hydrochloric acid and sodium hydroxide aqueous solutions used to adjust the system pH; water introduced by the acid and alkaline solutions is counted as deionized water. The preservation component consists of phenoxyethanol, 1,2-hexanediol, and ethylhexylglycerin in a mass ratio of 6:3:1. All three raw materials are commercially available cosmetic grade with a purity ≥98.0%.
[0052] The preparation process involves first hydrolyzing the Q unit with tetraethyl silicate, ethanol, deionized water, and 0.10 mol / L hydrochloric acid aqueous solution at 30 °C and 350 rpm for 1.50 h. Then, hexamethyldisiloxane is added for end-capping condensation, and the mixture is stirred at 55 °C for 3.00 h. The pH is adjusted to 7.50 using 0.10 mol / L sodium hydroxide aqueous solution. After phase separation, washing with water, and vacuum devolatilization, trimethylsilanoyloxysilicate is obtained. 100 parts by mass of trimethylsilanoyloxysilicate are taken, and 80 parts by mass of ethanol and 60 parts by mass of deionized water are added. The mixture is stirred at 55 °C for 3.00 h, allowed to stand for separation, and the silicate phase is collected. Vaporization is carried out at 95 °C and 0.001 MPa for 10.00 h to obtain low-volatility trimethylsilanoyloxysilicate. The total amount of octamethylcyclotetrasiloxane, decamethylcyclopentasiloxane, and dodecylcyclohexasiloxane is 0.30 wt%.
[0053] In the post-processing step, 100 parts by mass of low-volatility trimethylsiloxysilicate was added to 30 parts by mass of ethanol and 10 parts by mass of deionized water. The mixture was stirred at 700 rpm for 2.00 h at 70 °C to obtain a trimethylsiloxysilicate pre-dispersion. 4 parts by mass of PEG-12 polydimethylsiloxane were added to the pre-dispersion, and the mixture was stirred at 700 rpm for 3.00 h at 75 °C. The pH of the system was adjusted to 7.50 to obtain an interfacial pre-composite system. Subsequently, under a shear condition of 8000 rpm, 180 parts by mass of deionized water were added to the interfacial pre-composite system over 3.00 h to obtain a latex particle dispersion. The latex particle dispersion was aged at 60 °C for 6.00 h and filtered through a 100-mesh filter and a 0.80 μm filter membrane. The filtered dispersion system was used as the mother liquor for latex particles. The final composition was prepared according to the raw materials and proportions described in this embodiment. The preservation component was added and the pH value of the system was adjusted to 7.50. The mixture was stirred at 40°C for 2.00 h and then filtered again to obtain the preservation-type waterborne MQ organosilicon film-forming resin of this embodiment.
[0054] Quality testing methods and results: The particle size of the latex particles in this embodiment was determined using dynamic light scattering. The sample was diluted 200 times with deionized water, tested at 25℃, and repeated three times. The D50 was 500 nm, and the PDI was 0.35. The pH of the finished product was measured to be 7.50. After drying at 105℃ to constant weight, the solid content was measured to be 58.00 wt%. The apparent viscosity was measured to be 5000 mPa·s at 25℃ and 20 rpm using a rotational viscometer. After centrifugation and calculation of the supernatant components, the retention rate of PEG-12 polydimethylsiloxane was 95.00%. After storage at 45℃ for 8 weeks, the D50 change rate was 15.00%. Three batches were prepared repeatedly, with an inter-batch coefficient of variation of 5.00% for solid content and 10.00% for D50.
[0055] The key features of this embodiment are its high resin loading and high process strength. The trimethylsiloxysilicate content, phase-conversion emulsification shear strength, aging temperature, aging time, and storage treatment intensity are all in the high-value range, making it suitable for waterproof foundations, eyeliners, mascaras, and long-lasting lip makeup systems that require high film integrity, water resistance, and high film-forming capacity. By adding the water-based MQ silicone film-forming resin of this embodiment at 35.00 wt% of the total mass of the added system to a water-containing makeup matrix with a pH of 8.00, and stirring at 800 rpm for 30 minutes, a makeup sample with high film-forming resin content can be obtained.
[0056] Example 3 The key parameters and sample conditions of this embodiment are as follows: The preparation scale is 1000g of finished product, which is an aqueous MQ silicone film-forming resin that can be directly added to a makeup base. The finished product contains 40.00wt% trimethylsiloxysilicate, 6.00wt% PEG-12 polydimethylsiloxane, 46.00wt% deionized water, 8.00wt% ethanol, 0.00wt% pH adjustment component, and 0.00wt% preservation component. The M / Q molar ratio of trimethylsiloxysilicate is 0.80, and the silanol content is 2.20wt%. The tetraethyl silicate, hexamethyldisiloxane, ethanol, hydrochloric acid aqueous solution, sodium hydroxide, PEG-12 polydimethylsiloxane, and deionized water used in this embodiment are all commercially available or conventional laboratory reagents, and no brand or manufacturer-specific sources were used.
[0057] In the preparation process, tetraethyl silicate, ethanol, deionized water, and 0.10 mol / L hydrochloric acid aqueous solution were first added to a reactor and hydrolyzed at 28 °C and 320 rpm for 1.20 h to obtain the Q unit hydrolysis condensate. After adding hexamethyldisiloxane, condensation was carried out at 50 °C and 320 rpm for 2.50 h. The pH value was adjusted to 6.80 with 0.10 mol / L sodium hydroxide aqueous solution. After phase separation, water washing, and vacuum devolatilization, trimethylsilanoyl silicate was obtained. Subsequently, 100 parts by mass of trimethylsilanoyl silicate were taken, 45 parts by mass of ethanol and 30 parts by mass of deionized water were added, and the mixture was stirred at 40 °C for 1.50 h. After standing and layering, the silicate phase was taken and devolatilized at 75 °C and 0.010 MPa under reduced pressure for 6.00 h to obtain low-volatility trimethylsilanoyl silicate. The total amount of octamethylcyclotetrasiloxane, decamethylcyclopentasiloxane, and dodecylcyclohexasiloxane was found to be 0.15 wt%.
[0058] Subsequently, 100 parts by weight of low-volatility trimethylsiloxysilicate was added to 18 parts by weight of ethanol and 5 parts by weight of deionized water, and stirred at 600 rpm for 1.00 h at 55 °C to obtain a trimethylsiloxysilicate pre-dispersion. 12 parts by weight of PEG-12 polydimethylsiloxane were added to the pre-dispersion, and stirred at 600 rpm for 1.50 h at 60 °C, maintaining the pH at 6.50 to obtain an interfacial pre-composite system. 130 parts by weight of deionized water were added to the interfacial pre-composite system under a shearing condition of 4000 rpm over 1.50 h to induce reverse emulsification. The system was then aged at 45 °C for 3.00 h, filtered through a 100-mesh filter and a 0.80 μm filter membrane to obtain a latex particle mother liquor. The latex particle mother liquor was then formulated according to the final composition described in this embodiment to obtain the aqueous MQ organosilicon film-forming resin of this embodiment.
[0059] During quality testing, the sample in this embodiment was diluted 150 times with deionized water. The D50 was measured to be 260 nm using dynamic light scattering, and the PDI was 0.20. The test was repeated three times. The pH of the finished product was measured to be 6.50. After drying at 105℃ to constant weight, the solid content was measured to be 46.00 wt%. The apparent viscosity was measured to be 1200 mPa·s using a rotational viscometer at 25℃ and 20 rpm. Centrifugation analysis showed that the retention rate of PEG-12 polydimethylsiloxane was 78.00%. After storage at 45℃ for 8 weeks, the D50 change rate was 6.00%. Three batches were prepared repeatedly; the inter-batch coefficient of variation for solid content was 2.00%, and the inter-batch coefficient of variation for D50 was 4.00%.
[0060] Applicable Scenarios of This Embodiment This embodiment employs a medium resin content, a high ethanol residue control point, and medium shear emulsification conditions. The formulation, particle size, pH, and viscosity are within a relatively easy-to-process middle range, making it suitable for foundation, concealer, and long-lasting spray emulsion systems that require a balance of spreadability, quick drying, water resistance, and a supple film. The aqueous MQ silicone film-forming resin of this embodiment is added at 15.00 wt% of the total mass of the added system to a water-based cosmetic matrix with a pH of 6.80. Stirring at 700 rpm for 25 minutes yields a cosmetic sample with a medium resin content.
[0061] Example 4 I. Overall Preparation Arrangement and Target Product: A water-based MQ organosilicon film-forming resin was prepared with a target yield of 1000g. The final product, based on a total mass of 100wt%, consisted of 46.00wt% trimethylsiloxysilicate, 12.00wt% PEG-12 polydimethylsiloxane, 40.00wt% deionized water, 0.00wt% ethanol, 0.50wt% pH adjustment component, and 1.50wt% preservation component. In this embodiment, the M / Q molar ratio of trimethylsiloxysilicate was 0.95, the silanol content was 1.20wt%, and the preservation component was composed of phenoxyethanol and 1,2-hexanediol in a mass ratio of 7:3.
[0062] II. Preparation of Low-Volatile Trimethylsiloxane Silicate: Hydrolysis of tetraethyl silicate and condensation of hexamethyldisiloxane were carried out in a reactor at 30°C for 1.50 h, and at 52°C for 2.50 h. The pH was adjusted to 7.20 using a 0.10 mol / L sodium hydroxide aqueous solution. After phase separation, washing with water, and vacuum devolatilization, trimethylsiloxane silicate was obtained. 100 parts by mass of trimethylsiloxane silicate were added to 60 parts by mass of ethanol and 20 parts by mass of deionized water. The mixture was stirred at 50°C for 2.50 h, allowed to stand for separation, and the silicate phase was collected. Vacuum devolatilization was performed at 85°C and 0.005 MPa for 8.00 h to obtain low-volatility trimethylsiloxane silicate. Gas chromatography analysis showed that the total amount of octamethylcyclotetrasiloxane, decamethylcyclopentasiloxane, and dodecylcyclohexasiloxane was 0.05 wt%.
[0063] III. Interface Structure Construction and Aqueous Degradation: 100 parts by mass of low-volatility trimethylsiloxysilicate was added to 25 parts by mass of ethanol and 0 parts by mass of deionized water. The mixture was stirred at 650 rpm for 1.50 h at 65 °C to obtain a trimethylsiloxysilicate pre-dispersion. 20 parts by mass of PEG-12 polydimethylsiloxane were added to the pre-dispersion, and the mixture was stirred at 650 rpm for 2.50 h at 68 °C. The pH of the system was adjusted to 7.20 to obtain an interfacial pre-composite system. Subsequently, under a shear condition of 6500 rpm, 110 parts by mass of deionized water were added to the interfacial pre-composite system over 2.00 h to form a trimethylsiloxysilicate-PEG-12 polydimethylsiloxane interfacial modified latex particle dispersion.
[0064] IV. Stabilization, Preservation, and Filtration: The latex particle dispersion was aged at 50°C for 4.50 hours, filtered through a 100-mesh filter, and then filtered again through a 0.80 μm filter membrane. The filtered dispersion was used as the latex particle mother liquor. The final composition was prepared according to the instructions in this embodiment, and the preservation component was added. The pH of the system was adjusted to 7.50 using hydrochloric acid and sodium hydroxide solutions. The mixture was stirred at 400 rpm for 2.00 hours at 40°C, and then filtered again to obtain the preservation-type aqueous MQ organosilicon film-forming resin of this embodiment.
[0065] V. Quality Testing Methods and Results: Before dynamic light scattering testing, the sample was diluted 150 times with deionized water and gently inverted to mix. The test temperature was 25℃, and the results were repeated 3 times. The D50 was measured to be 120nm, and the PDI was 0.12. The pH value of the finished product was measured to be 7.50 using a pH meter. After drying at 105℃ to constant weight, the solid content was measured to be 58.00wt%. The apparent viscosity was measured to be 2500mPa·s using a rotational viscometer at 25℃ and 20rpm. After centrifugation and calculation of the supernatant components, the retention rate of PEG-12 polydimethylsiloxane was 90.00%. After storage at 45℃ for 8 weeks, the D50 change rate was 3.20%. Three batches were prepared repeatedly, and the inter-batch coefficient of variation for solid content was 1.50%, and the inter-batch coefficient of variation for D50 was 2.00%.
[0066] VI. Process Characteristics and Application Directions of this Embodiment: This embodiment employs a relatively high PEG-12 polydimethylsiloxane content, high interfacial pre-composite strength, and high preservation treatment strength, making it suitable for water-based makeup systems requiring good latex particle interfacial stability, high emulsification compatibility, and a good balance of water resistance and film feel. The water-based MQ silicone film-forming resin of this embodiment is added to a water-containing makeup matrix with a pH of 7.20 at 20.00 wt% of the total mass of the added system. Stirring at 700 rpm for 30 min yields film-forming samples suitable for long-lasting foundations and water-based lip gloss bases.
[0067] In the following comparative examples, the preparation conditions of the latex granule mother liquor are the same as those in Example 1 unless otherwise specified; the adjustments to the composition of the finished products in the comparative examples are implemented in accordance with the aforementioned latex granule mother liquor and finished product ingredient ratio.
[0068] Comparative Example 1: Basically the same as Example 1, except that the content of trimethylsiloxysilicate in the finished product was adjusted to 25.00 wt%, and the content of deionized water as a supplementary phase was adjusted to 72.80 wt%. The key conditions were maintained as follows: PEG-12 polydimethylsiloxane 2.00 wt%, ethanol 0.00 wt%, pH adjustment component 0.00 wt%, preservation component 0.20 wt%, M / Q molar ratio 0.55, silanol content 4.50 wt%, low volatility pretreatment temperature 25℃, vacuum devolatilization 60℃ and 0.020 MPa, A2 ethanol 8 parts by mass, A3 PEG-12 polydimethylsiloxane 4 parts by mass, A4 shear speed 1500 rpm, A4 deionized water 80 parts by mass, A5 aging temperature 30℃, A5 aging time 1.00 h, and finished product pH value 5.50.
[0069] Comparative Example 2: Basically the same as Example 1, except that the content of trimethylsiloxysilicate in the finished product was adjusted to 60.00 wt%, and the content of deionized water as a supplementary phase was adjusted to 37.80 wt%. The key conditions were maintained as follows: PEG-12 polydimethylsiloxane 2.00 wt%, ethanol 0.00 wt%, pH adjustment component 0.00 wt%, preservation component 0.20 wt%, M / Q molar ratio 0.55, silanol content 4.50 wt%, low volatility pretreatment temperature 25℃, vacuum devolatilization 60℃ and 0.020 MPa, A2 ethanol 8 parts by mass, A3 PEG-12 polydimethylsiloxane 4 parts by mass, A4 shear speed 1500 rpm, A4 deionized water 80 parts by mass, A5 aging temperature 30℃, A5 aging time 1.00 h, and finished product pH value 5.50.
[0070] Comparative Example 3: Basically the same as Example 1, except that the content of PEG-12 polydimethylsiloxane in the finished product was adjusted to 0.50wt%, and deionized water was adjusted to 69.30wt% as a supplementary phase; the key conditions were maintained as follows: trimethylsiloxysilicate 30.00wt%, ethanol 0.00wt%, pH adjustment component 0.00wt%, preservation component 0.20wt%, M / Q molar ratio 0.55, silanol content 4.50wt%, low volatility pretreatment temperature 25℃, vacuum devolatilization 60℃ and 0.020MPa, A2 ethanol 8 parts by mass, A4 shear speed 1500rpm, A4 deionized water 80 parts by mass, A5 aging temperature 30℃, A5 aging time 1.00h, and finished product pH value 5.50.
[0071] Comparative Example 4: Basically the same as Example 1, except that the content of PEG-12 polydimethylsiloxane in the finished product was adjusted to 16.00 wt%, and deionized water was adjusted to 53.80 wt% as a make-up phase; the key conditions were maintained as follows: trimethylsiloxysilicate 30.00 wt%, ethanol 0.00 wt%, pH adjustment component 0.00 wt%, preservation component 0.20 wt%, M / Q molar ratio 0.55, silanol content 4.50 wt%, low volatility pretreatment temperature 25℃, vacuum devolatilization 60℃ and 0.020 MPa, A2 ethanol 8 parts by mass, A4 shear speed 1500 rpm, A4 deionized water 80 parts by mass, A5 aging temperature 30℃, A5 aging time 1.00 h, and finished product pH value 5.50.
[0072] Comparative Example 5: Basically the same as Example 1, except that the M / Q molar ratio of trimethylsiloxysilicate was adjusted to 0.40; the key conditions were maintained as follows: 30.00 wt% trimethylsiloxysilicate, 2.00 wt% PEG-12 polydimethylsiloxane, 67.80 wt% deionized water, 0.00 wt% ethanol, 0.00 wt% pH adjustment component, 0.20 wt% preservation component, 4.50 wt% silanol content, low volatility pretreatment temperature 25°C, vacuum devolatilization at 60°C and 0.020 MPa, 8 parts by mass of A2 ethanol, 4 parts by mass of A3 PEG-12 polydimethylsiloxane, 1500 rpm shearing speed, 80 parts by mass of A4 deionized water, 30°C aging temperature, 1.00 h aging time, and pH value of the finished product 5.50.
[0073] Comparative Example 6: Basically the same as Example 1, except that the M / Q molar ratio of trimethylsiloxysilicate was adjusted to 1.25; the key conditions were maintained as follows: 30.00 wt% trimethylsiloxysilicate, 2.00 wt% PEG-12 polydimethylsiloxane, 67.80 wt% deionized water, 0.00 wt% ethanol, 0.00 wt% pH adjustment component, 0.20 wt% preservation component, 4.50 wt% silanol content, low volatility pretreatment temperature 25°C, vacuum devolatilization at 60°C and 0.020 MPa, 8 parts by mass of A2 ethanol, 4 parts by mass of A3 PEG-12 polydimethylsiloxane, 1500 rpm shear speed, 80 parts by mass of A4 deionized water, 30°C aging temperature, 1.00 h aging time, and pH value of the finished product 5.50.
[0074] Comparative Example 7: Basically the same as Example 1, except that the shear speed of the reverse emulsification step in A4 was adjusted to 800 rpm; the key conditions were maintained as follows: 30.00 wt% trimethylsiloxysilicate, 2.00 wt% PEG-12 polydimethylsiloxane, 67.80 wt% deionized water, 0.00 wt% ethanol, 0.00 wt% pH adjustment component, 0.20 wt% preservation component, M / Q molar ratio 0.55, silanol content 4.50 wt%, low volatility pretreatment temperature 25°C, vacuum devolatilization at 60°C and 0.020 MPa, 8 parts by mass of ethanol in A2, 4 parts by mass of PEG-12 polydimethylsiloxane in A3, 80 parts by mass of deionized water in A4, A4 addition time 0.50 h, A5 aging temperature 30°C, A5 aging time 1.00 h, and finished product pH value 5.50.
[0075] Comparative Example 8: Basically the same as Example 1, except that the aging temperature of the A5 aging stabilization step was adjusted to 25°C; the key conditions were maintained as follows: 30.00 wt% trimethylsiloxysilicate, 2.00 wt% PEG-12 polydimethylsiloxane, 67.80 wt% deionized water, 0.00 wt% ethanol, 0.00 wt% pH adjustment component, 0.20 wt% preservation component, M / Q molar ratio 0.55, silanol content 4.50 wt%, low volatility pretreatment temperature 25°C, vacuum devolatilization 60°C and 0.020 MPa, 8 parts by mass of A2 ethanol, 4 parts by mass of A3 PEG-12 polydimethylsiloxane, 1500 rpm shearing speed of A4, 80 parts by mass of A4 deionized water, A4 addition time 0.50 h, A5 aging time 1.00 h, and finished product pH value 5.50.
[0076] Comparative Example 9: Essentially the same as Example 1, except that PEG-12 polydimethylsiloxane was not added. The PEG-12 polydimethylsiloxane content in the finished product was 0.00 wt%, with deionized water used as a supplementary phase to adjust to 69.80 wt%. No PEG-12 polydimethylsiloxane interfacial pre-composite was performed. Key conditions were maintained as follows: trimethylsiloxysilicate 30.00 wt%, ethanol 0.00 wt%, pH adjustment component 0.00 wt%, preservation component 0.20 wt%, M / Q molar ratio 0.55, silanol content 4.50 wt%, low-volatility pretreatment temperature 25°C, vacuum devolatilization 60°C and 0.020 MPa, A2 ethanol 8 parts by mass, A4 shear speed 1500 rpm, A4 deionized water 80 parts by mass, A5 aging temperature 30°C, A5 aging time 1.00 h, and finished product pH 5.50. This comparative example was used to investigate the synergistic relationship between trimethylsiloxysilicate and PEG-12 polydimethylsiloxane.
[0077] Comparative Example 10: Essentially the same as Example 1, except that trimethylsiloxysilicate was not added. The trimethylsiloxysilicate content in the finished product was 0.00 wt%, with deionized water added as a supplementary phase to adjust to 97.80 wt%. The system retained 2.00 wt% PEG-12 polydimethylsiloxane and 0.20 wt% of other components, and no trimethylsiloxysilicate-PEG-12 polydimethylsiloxane interface-modified latex particles were formed. Key conditions were maintained as follows: 0.00 wt% ethanol, 0.00 wt% pH adjustment component, low-volatility pretreatment not included in the finished product components, A3 stirring temperature 50°C, A3 stirring time 0.50 h, A4 shear speed 1500 rpm, A4 deionized water 80 parts by mass, A5 aging temperature 30°C, A5 aging time 1.00 h, and finished product pH 5.50. This comparative example was used to investigate the synergistic relationship between trimethylsiloxysilicate and PEG-12 polydimethylsiloxane.
[0078] Comparative Example 11: Basically the same as Example 1, except that the interface pre-composite step is omitted. Before step A4, PEG-12 polydimethylsiloxane is added to the trimethylsiloxysilicate pre-dispersion and shear emulsification is performed immediately. The heating and stirring interface pre-composite treatment described in step A3 is not performed. Deionized water is still added continuously in the same way as in step A4 of Example 1. The key conditions were maintained as follows: 30.00 wt% trimethylsiloxysilicate, 2.00 wt% PEG-12 polydimethylsiloxane, 67.80 wt% deionized water, 0.00 wt% ethanol, 0.00 wt% pH adjustment component, 0.20 wt% preservation component, M / Q molar ratio 0.55, silanol content 4.50 wt%, low volatility pretreatment temperature 25℃, vacuum devolatilization 60℃ and 0.020 MPa, A2 ethanol 8 parts by mass, A4 shear speed 1500 rpm, A4 deionized water 80 parts by mass, A4 addition time 0.50 h, A5 aging temperature 30℃, A5 aging time 1.00 h, and finished product pH value 5.50. This comparative example was used to investigate the synergistic relationship between the interfacial precomposite sequence and the construction of interfacial modified latex particles.
[0079] Characterization and performance testing: The latex particle size and distribution of the aqueous MQ silicone film-forming resins in Examples 1–4 and all comparative examples were tested to evaluate the effects of interfacial precomposite, PEG-12 polydimethylsiloxane content, and shear conditions on D50, PDI, and the rate of change of D50 after 8 weeks of storage at 45°C. The principle is based on the Brownian motion of dispersed particles causing fluctuations in scattered light intensity. A dynamic light scattering instrument was used. Samples were diluted 100–200 times with deionized water and equilibrated at 25°C for 2 minutes. The experiment was repeated n=3 times, and the mean D50, standard deviation D50, mean PDI, standard deviation PDI, mean D50 rate of change, and standard deviation of D50 rate of change were recorded. The arithmetic mean of three parallel measurements was used as the judgment value for D50, PDI, and the rate of change of D50. Lower D50 rate of change and PDI indicate better dispersion stability. The DLS method can be referenced within the scope of ISO 22412:2017.
[0080] Solid content, pH value, and apparent viscosity were tested for each sample to evaluate the composition, storage, pH post-treatment, and processing suitability of the finished product. Solid content was measured by drying to constant weight at 105℃. pH value was measured using a pH meter calibrated with pH 4.00, pH 6.86, and pH 9.18 buffer solutions. Apparent viscosity was measured using a rotational viscometer or rotational rheometer at 25℃ and 20 rpm (n=3). The mean solid content, standard deviation of solid content, mean pH value, standard deviation of pH value, mean apparent viscosity, and standard deviation of apparent viscosity were recorded. Viscosity within the target range and low batch-to-batch variation indicated good processing suitability. General principles of rotational rheology can be referenced from ISO 3219-2:2021.
[0081] The residual ethanol content and total amounts of D4, D5, and D6 were tested on low-volatility trimethylsiloxysilicate and finished resin to evaluate the contribution of low-volatility pretreatment and reduced-pressure devolatilization conditions to residue control. The GC-FID or GC-MS internal standard method was used. Samples were quantitatively diluted with a suitable solvent, and an internal standard was added. The residual ethanol content and the total amounts of octamethylcyclotetrasiloxane, decamethylcyclopentasiloxane, and dodecylcyclohexasiloxane were calculated based on retention time and calibration curves (n=3). The mean residual ethanol content, standard deviation of residual ethanol content, mean total D4 / D5 / D6, and standard deviation of total D4 / D5 / D6 were recorded. The total amounts of D4 / D5 / D6 were expressed as the mass of trimethylsiloxysilicate solids; lower values indicated more adequate residue control.
[0082] Standard films were prepared for each sample and their water resistance and film-forming properties were tested. The purpose was to evaluate the balance between the hydrophobic film-forming contribution of trimethylsiloxysilicate and the interfacial stabilizing effect of PEG-12 polydimethylsiloxane. The samples were coated on an inert substrate with the same solid content, and the wet film thickness was 100 μm. The films were dried at 25 °C and 50% relative humidity for 24 h. After weighing the dry film, the films were immersed in deionized water at 25 °C for 30 min. The films were then removed, wiped gently, and dried for another 1 h. The mass retention rate after water immersion was calculated (n=3). The mean and standard deviation of the mass retention rate after water immersion were recorded. The higher the value, the better the water resistance and film-forming properties.
[0083] The abrasion resistance and skin comfort of the film-forming samples after adding watercolor-containing cosmetic matrix were tested to evaluate makeup retention, anti-transfer, and low-resistance skin feel. The samples were added to watercolor-containing cosmetic matrix with pH 5.50–8.00 according to the specified ratio in the example, coated to form a film, and dried for 24 hours. The film was rubbed 100 times under a fixed load using a reciprocating friction device, and the mass loss was recorded. At the same time, the kinetic friction coefficient between the dry film and the same batch of artificial skin substitute substrate was measured using a friction coefficient tester (n=3). The mean and standard deviation of friction mass loss, and the mean and standard deviation of kinetic friction coefficient were recorded. The friction mass loss and kinetic friction coefficient were used as the basis for comparing the abrasion resistance and skin comfort of different samples.
[0084] The retention rate of PEG-12 polydimethylsiloxane in interface-modified latex particles was tested to evaluate whether the synergistic units formed a stable interface distribution. The sample was centrifuged to separate the latex particle-enriched phase and the supernatant phase. The content of free PEG-12 polydimethylsiloxane in the supernatant phase was determined using quantitative methods for total organic carbon and siloxanes or adaptive chromatography. The retention rate in the latex particles was calculated based on the feed amount (n=3). The PEG-12 polydimethylsiloxane retention rate was calculated as follows: Retention rate = (PEG-12 polydimethylsiloxane feed mass - free PEG-12 polydimethylsiloxane in the supernatant phase) / PEG-12 polydimethylsiloxane feed mass × 100%. This retention rate characterizes the degree of PEG-12 polydimethylsiloxane retention in the latex particle-enriched phase and is not used as the sole criterion for determining its location on the latex particle surface.
[0085] To verify the comprehensive effects of the waterborne MQ organosilicon film-forming resin described in this invention on dispersion stability, water-resistant film formation, film layer resistance to damage, and skin feel, dynamic light scattering particle size test, film water resistance test, friction resistance test, dynamic friction coefficient test, component content effect test, and macroscopic and microscopic morphology observation were conducted on Example 1 and related comparative examples. The test results show that this invention, through the matching of the hydrophobic film-forming network formed by trimethylsiloxysilicate and the interfacial stabilizing effect of PEG-12 polydimethylsiloxane, combined with interfacial pre-composite, phase inversion emulsification, and low-volatility treatment, can form a film layer with good water resistance, friction resistance, and skin comfort while ensuring stable dispersion of latex particles. This effectively solves the problem of difficulty in simultaneously achieving dispersion stability and water resistance, and film layer integrity and skin comfort in existing waterborne MQ organosilicon film-forming systems.
[0086] First, from the perspective of the dispersion state of latex particles, Figures 1 to 3 The particle size distribution characteristics of Example 1, Comparative Example 7 and Comparative Example 11 were compared. Figure 1 The DLS particle size distribution diagram of the interface-modified latex particles shows that the particle size distribution peaks in Example 1 are concentrated and narrow, with a D50 of approximately 80 nm and a PDI of approximately 0.08. This indicates that the latex particles in the system are concentrated in size, and no obvious large particle agglomeration peaks are observed. In contrast, the D50 of Comparative Example 7 is approximately 950 nm, and the D50 of Comparative Example 11 is approximately 380 nm. Both of these particle sizes are significantly shifted towards larger particle sizes, and the distribution width increases. This suggests that under mismatched shear dispersion conditions or without effective interfacial pre-composite treatment, hydrophobic resin components such as trimethylsiloxysilicate are more prone to local enrichment, leading to latex particle agglomeration or insufficient dispersion. Therefore, the interface-stabilizing components and emulsification dispersion process used in this invention do not simply improve appearance uniformity, but rather reduce the tendency of latex particle agglomeration at the nanoscale, enabling the waterborne MQ organosilicon film-forming resin to form a more stable dispersion basis.
[0087] Further integration Figure 2 As shown in the cumulative distribution diagram of DLS particle size, the cumulative distribution curve of Example 1 rises rapidly in the smaller particle size range, indicating that its latex particles are mainly concentrated in the nanoparticle size range and the particle size dispersion is low; while the cumulative distribution curves of Comparative Example 7 and Comparative Example 11 shift significantly to the right and the rising slope decreases, indicating that there is a large proportion of large-size particles or agglomerates in the system. Figure 3 The D50 mean comparison chart further quantifies the above differences: the D50 of Example 1 is approximately 80 nm, which is about 91.6% lower than that of Comparative Example 7 (approximately 950 nm) and about 78.9% lower than that of Comparative Example 11 (approximately 380 nm). This result indicates that, under the same or similar compositional conditions, relying solely on subsequent stirring or ordinary emulsification cannot effectively solve the dispersion stability problem of hydrophobic MQ resin in aqueous systems. This invention, through interfacial pre-composite processing, mixes PEG-12 polydimethylsiloxane with a trimethylsiloxysilicate pre-dispersion to form an interfacial pre-composite system, followed by phase inversion emulsification to form stable latex particles. This significantly reduces the median particle size and narrows the particle size distribution. The above results corroborate each other from three aspects: particle size intensity distribution, cumulative distribution, and D50 mean, proving that the present invention can effectively improve the dispersion stability of waterborne MQ organosilicon film-forming resin.
[0088] Based on obtaining a stable latex particle dispersion system, we further investigated its water resistance, film integrity, and friction resistance after film formation. Figure 4 The chart shows the mass retention rate after water immersion, used to evaluate the water-resistant film-forming effect of Example 1, Comparative Example 5, and Comparative Example 6. The results show that the mass retention rate after water immersion for Example 1 is approximately 86.5%, for Comparative Example 5 it is approximately 94.0%, and for Comparative Example 6 it is approximately 70.0%. From the perspective of a single water resistance index, Comparative Example 5 has a higher mass retention rate, but considering subsequent friction and skin feel results, its film layer tends to be denser or stiffer, making it difficult to maintain user comfort. The mass retention rate of Comparative Example 6 is significantly lower, indicating that its film layer is more prone to swelling, peeling, or structural damage under water immersion conditions. Although Example 1 did not pursue the highest single mass retention rate, its mass retention rate is about 16.5 percentage points higher than that of Comparative Example 6, indicating that while introducing interfacial hydrophilic stabilizing components, the present invention did not lead to a significant deterioration in the water resistance of the film layer, but rather achieved a reasonable balance between the hydrophobic MQ film-forming network and the stabilizing effect of the hydrophilic interface.
[0089] Figure 5The graph shows a comparison of frictional mass loss, further used to evaluate the film's resistance to frictional damage after water immersion and film formation. The frictional mass loss of Example 1 was approximately 8.5%, lower than Comparative Example 5's approximately 9.8%, and significantly lower than Comparative Example 6's approximately 20.0%. Compared to Comparative Example 6, the frictional mass loss of Example 1 was reduced by approximately 57.5%; compared to Comparative Example 5, the frictional mass loss of Example 1 also decreased. These results indicate that the film formed in Example 1 not only has good water retention but also maintains high structural integrity under external friction, making it less prone to pulverization, detachment, or large-area damage. Figure 4 and Figure 5 It can be seen that the present invention does not achieve water resistance by simply improving the hydrophobicity of the film layer, but rather by rationally controlling the relationship between the hydrophobic film-forming network and the interface stabilizing layer, so that the film layer still has good continuity and anti-friction properties after water immersion, thereby solving the technical contradictions in the traditional system of "improved water resistance but film layer becomes hard and easily abrasive" or "improved skin feel but decreased water resistance and anti-friction properties of the film layer".
[0090] Furthermore, Figure 6 The graph shows the comparison of kinetic friction coefficients, used to evaluate the user comfort of Examples 1, 5, and 6 from the perspective of skin feel. The kinetic friction coefficient of Example 1 is approximately 0.38, that of Comparative Example 5 is approximately 0.75, and that of Comparative Example 6 is approximately 0.29. The higher kinetic friction coefficient of Comparative Example 5 indicates greater surface friction resistance, potentially resulting in a rough, dragging, or stiff feel during use. The lower kinetic friction coefficient of Comparative Example 6 indicates a smoother surface, but considering its approximately 70.0% mass retention rate after water immersion and approximately 20.0% frictional mass loss, the system's film structure stability is insufficient, making it difficult to meet the requirements for long-lasting film formation. The kinetic friction coefficient of Example 1 falls between these two, avoiding both the roughness and stiffness caused by excessive friction and the looseness or excessive smoothness associated with excessively low friction. This demonstrates that the waterborne MQ organosilicon film-forming resin obtained in this invention achieves a comprehensive balance between water resistance, film formation, resistance to friction damage, and skin feel comfort, demonstrating superior overall application value compared to single performance optimization schemes.
[0091] To further illustrate the impact of PEG-12 polydimethylsiloxane content on the aforementioned overall performance, Figure 7The effect of varying PEG-12 polydimethylsiloxane content on the mass retention rate and frictional mass loss after water immersion was investigated. This test was based on Example 1, with the PEG-12 polydimethylsiloxane content varying from 1.00–15.00 wt% and the final total mass being made up with deionized water; all other composition and preparation conditions remained consistent. The results showed that when the PEG-12 polydimethylsiloxane content increased from 1.00 wt% to 7.00 wt%, the mass retention rate after water immersion increased from 82.0% to 91.5%, and the frictional mass loss decreased from 13.5% to 5.8%. This change indicates that an appropriate amount of PEG-12 polydimethylsiloxane can improve the interfacial wetting and dispersion stability between the hydrophobic MQ resin and the aqueous phase, which is beneficial for forming a more uniform particle size and more continuous film-forming latex particle system, thereby improving the film's retention capacity after water immersion and reducing the degree of frictional damage. Meanwhile, the results also indicate that PEG-12 polydimethylsiloxane is not used merely as a common emulsifying agent in this invention, but participates in the regulation of film structure through interfacial matching with trimethylsiloxysilicate; its content needs to be coordinated with the proportion of hydrophobic film-forming resin in order to achieve comprehensive optimization between stabilizing emulsion dispersion, maintaining water resistance and improving film flexibility. Figure 7 The results further demonstrate that by limiting and optimizing the ratio between the interface stabilizing component and the MQ hydrophobic resin, the present invention can effectively avoid dispersion instability caused by insufficient hydrophilic components, and can also suppress the risk of weakened water resistance that may be caused by excessive hydrophilic interface components.
[0092] In addition to particle size testing and performance testing, Figure 8 By comparing macroscopic optical photographs of the final product of Example 1 and the final product of Comparative Example 11, the influence of the interface pre-composite step on the dispersion stability of waterborne MQ organosilicon film-forming resin latex particles was further verified. Figure 8 Image a is a macroscopic optical photograph of the final product of Example 1, an aqueous MQ organosilicon film-forming resin latex particle dispersion. This sample consists of 30.00 wt% trimethylsiloxysilicate, 2.00 wt% PEG-12 polydimethylsiloxane, 67.80 wt% deionized water, and 0.20 wt% phenoxyethanol. Its D50 is 80 nm, PDI is 0.08, solid content is 32.00 wt%, and pH is 5.50. These parameters indicate that Example 1 can form an aqueous latex particle dispersion system with uniform appearance, narrow particle size distribution, suitable solid content, and a weakly acidic pH. Figure 8b is a macroscopic optical photograph of the final product of Comparative Example 11. This sample has the same nominal composition as Example 1, but the interfacial pre-composite step of trimethylsiloxysilicate and PEG-12 polydimethylsiloxane was omitted. A comparison of the appearance and particle size results shows that even with the same nominal composition, without the interfacial pre-composite process, PEG-12 polydimethylsiloxane is difficult to fully mix with the trimethylsiloxysilicate pre-dispersion before emulsification and form a stable interfacial pre-composite system. This makes it easier to form localized large particles, agglomerates, or unevenly dispersed areas during the subsequent phase-conversion emulsification process. This demonstrates that the interfacial pre-composite, phase-conversion emulsification, and aging stabilization processes in this invention have a synergistic effect, jointly contributing to a low-viscosity, narrow-particle-size, and storage-stable aqueous MQ organosilicon film-forming resin system.
[0093] Furthermore, Figure 9 The microstructure of the final product of Example 1 and the final product of Comparative Example 11 after dry deposition was observed by scanning electron microscopy, which was used to verify the stable film formation mechanism of the present invention from the perspective of particle packing and dry film structure. Figure 9 a is a low-magnification scanning electron microscope image of the final product of Example 1. It can be seen that a relatively uniform latex particle deposition area is formed after drying. Combined with the filtration process of a 0.80 μm filter membrane, it shows that large-sized flocs in the system are effectively controlled. Figure 9 b is a low-magnification scanning electron microscope image of the final product of Comparative Example 11, used to compare whether local agglomeration, uneven deposition, or decreased dry film continuity occurred in the system after the interface pre-composite was removed. Figure 9 c is a scanning electron microscope image of the final product of Example 1. The local latex particle packing state corresponds to the dynamic light scattering test results with D50 of 80 nm and PDI of 0.08, indicating that Example 1 exhibits good particle size uniformity in both liquid dispersion and dry deposition states. Figure 9 Image d is a mid-magnification scanning electron microscope image of the final product of Comparative Example 11, used to compare the local particle packing uniformity and agglomeration state. Figure 9 e is a high-magnification scanning electron microscope image of the final product of Example 1, which further reveals the local morphology, particle boundaries, and dry packing details of the nano-latex particles, and corroborates the particle size distribution results obtained from dynamic light scattering tests. The above microstructure results are consistent with... Figures 1 to 3 DLS particle size analysis and Figures 4 to 6 The film-forming performance test results corroborate each other, indicating that the latex particles obtained by the present invention not only have good dispersion stability in the aqueous phase, but also can be effectively transformed into a film layer with complete structure, water resistance and suitable surface friction characteristics during the film-forming process.
[0094] In conclusion, Figures 1 to 9The effectiveness of this invention was demonstrated at multiple levels, including latex particle formation, particle size distribution control, film water resistance, film anti-friction damage ability, skin comfort, influence of component ratio, macroscopic stability, and microscopic morphology verification. Example 1, through compositional matching of 30.00 wt% trimethylsiloxysilicate, 2.00 wt% PEG-12 polydimethylsiloxane, 67.80 wt% deionized water, and 0.20 wt% phenoxyethanol, combined with interfacial pre-composite treatment, phase inversion emulsification, and low-volatility treatment, yielded an aqueous MQ organosilicon film-forming resin latex particle dispersion with a D50 of approximately 80 nm, a PDI of approximately 0.08, a solid content of approximately 32.00 wt%, and a pH of approximately 5.50. Compared to the comparative example that did not achieve sufficient interfacial stability or did not undergo interfacial pre-composite treatment, this system significantly reduced the latex particle size and distribution width; compared to the comparative example that simply improved water resistance or simply improved slip feel, it also achieved a better balance between mass retention rate, frictional mass loss, and dynamic friction coefficient after water immersion. Therefore, this invention can effectively alleviate or even solve the technical problems of existing waterborne MQ organosilicon film-forming resins, which are difficult to balance dispersion stability and water resistance, and difficult to unify film structure integrity and skin comfort. It has clear implementation effects and application value.
[0095] Table 1 Performance of Examples and Comparative Examples
[0096] As can be seen from the performance of the examples and comparative examples in Table 1, Examples 1–4 show a relatively balanced trend in terms of particle size distribution, D50 change rate after storage, water-resistant film formation, triboelectric mass loss, and PEG-12 polydimethylsiloxane retention rate. In the conventional comparative examples, when the trimethylsiloxysilicate content deviates, the M / Q molar ratio deviates, the shear speed is too low, or the aging temperature is insufficient, some indicators can be maintained, but the overall stability, water resistance, or skin feel proxy indicators decrease. In the synergistic comparative examples, after removing PEG-12 polydimethylsiloxane, removing trimethylsiloxysilicate, or canceling the interfacial precomposite, dispersion, film formation, or PEG-12 polydimethylsiloxane retention rate cannot be maintained simultaneously, indicating that the inherently contradictory properties require interfacial synergy and ratio matching for support.
[0097] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and not to limit it. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that any equivalent structural transformations made under the concept of the present invention and using the contents of the specification and drawings of the present invention should be covered within the scope of protection of the claims of the present invention.
Claims
1. A water-based MQ organosilicon film-forming resin, characterized in that, Based on a final total mass of 100 wt% of the aqueous MQ organosilicon film-forming resin, it consists of the following components: 30.00–55.00 wt% trimethylsiloxysilicate; 2.00–12.00 wt% of PEG-12 polydimethylsiloxane; 40.00–68.00 wt% deionized water; 0–8.00 wt% ethanol; 0–0.50 wt% pH adjusting component; Preservation components: 0–1.50 wt%; The content of each component is selected such that the total content of the aqueous MQ organosilicon film-forming resin is 100 wt%. The trimethylsiloxane silicate has an M / Q molar ratio of 0.55–1.10 and a silanol content of 0.30–4.50 wt%.
2. The aqueous MQ organosilicon film-forming resin according to claim 1, characterized in that, The trimethylsiloxane-PEG-12 polydimethylsiloxane interface-modified latex particles have a D50 of 80–500 nm and a PDI of 0.08–0.35, and the aqueous MQ organosilicon film-forming resin has a pH of 5.50–7.
50. The D50 and PDI are the arithmetic mean of three parallel determinations performed using the same test method.
3. The aqueous MQ organosilicon film-forming resin according to claim 1, characterized in that, The trimethylsiloxane-PEG-12 polydimethylsiloxane interface-modified latex particles are prepared by the following steps: A1. Steps for providing trimethylsiloxysilicate: providing trimethylsiloxysilicate having an M / Q molar ratio of 0.55–1.10 and a silanol content of 0.30–4.50 wt%; A2. Pre-dispersion step: The trimethylsiloxysilicate is mixed with ethanol and / or deionized water and pre-dispersion is performed to obtain a trimethylsiloxysilicate pre-dispersion solution; A3. Interface pre-composite step: PEG-12 polydimethylsiloxane is added to the trimethylsiloxane pre-dispersion to allow the PEG-12 polydimethylsiloxane to undergo interface pre-composite with the trimethylsiloxane to obtain an interface pre-composite system; A4. Reverse emulsification step: Under shear conditions, deionized water is added to the interfacial precomposite system to cause reverse emulsification of the system, forming a trimethylsiloxysilicate-PEG-12 polydimethylsiloxane interfacial modified latex particle dispersion. A5. Aging stabilization step: The trimethylsiloxysilicate-PEG-12 polydimethylsiloxane interface-modified latex particle dispersion is subjected to aging treatment; A6. Filtration and granulation steps: Filter the aged dispersion to obtain a trimethylsiloxysilicate-PEG-12 polydimethylsiloxane interface-modified latex particle dispersion system. A7. Preservation and pH Post-treatment Steps: The dispersion system obtained in step A6 is subjected to preservation component addition and pH adjustment treatment to obtain a preservation-type waterborne MQ organosilicon film-forming resin.
4. The aqueous MQ organosilicon film-forming resin according to claim 3, characterized in that, In step A1, the trimethylsiloxysilicate is provided in the following manner: Tetraethyl silicate, ethanol, deionized water and hydrochloric acid aqueous solution were mixed and hydrolyzed to obtain Q unit hydrolysis condensate; Add hexamethyldisiloxane to the hydrolysis condensate of the Q unit and condense it to obtain a trimethylsiloxysilicate reaction solution. The pH of the trimethylsiloxysilicate reaction solution was adjusted to 6.00–7.50 using sodium hydroxide. The pH-adjusted system was subjected to phase separation, water washing, and vacuum devolatilization to obtain trimethylsilyloxysilicate. The resulting trimethylsiloxane silicate has an M / Q molar ratio of 0.55–1.10, a silanol content of 0.30–4.50 wt%, and a residual ethanol content of 0.05–5.00 wt%.
5. The aqueous MQ organosilicon film-forming resin according to claim 3 or 4, characterized in that, In step A1, the trimethylsiloxysilicate undergoes a low-volatility pretreatment before proceeding to step A2. This low-volatility pretreatment includes: Trimethylsiloxane silicate was dispersed in a mixture of ethanol and deionized water and stirred. After standing and separating into layers or by centrifugation, the silicate phase is taken; The silicate phase was subjected to vacuum devolatilization to obtain low-volatility trimethylsiloxy silicate; The total amount of octamethylcyclotetrasiloxane, decamethylcyclopentasiloxane and dodecylcyclohexasiloxane in the low-volatility trimethylsiloxysilicate is 0.02–0.50 wt%.
6. The aqueous MQ organosilicon film-forming resin according to claim 3, characterized in that, Steps A2 to A7 include the following conditions: In step A2, the trimethylsiloxysilicate is mixed with at least one of ethanol and deionized water and heated and stirred to obtain the trimethylsiloxysilicate predispersant. In step A3, PEG-12 polydimethylsiloxane is added to the trimethylsiloxysilicate predispersant, and the mixture is heated, stirred, and the pH is adjusted to obtain the interface precomposite system. In step A4, deionized water is added to the interfacial precomposite system under shear conditions to cause the system to undergo reverse emulsification, thereby obtaining the trimethylsiloxysilicate-PEG-12 polydimethylsiloxane interfacial modified latex particle dispersion. In step A5, the trimethylsiloxysilicate-PEG-12 polydimethylsiloxane interface-modified latex particle dispersion is subjected to aging treatment. In step A6, the aged dispersion is filtered to obtain the trimethylsiloxysilicate-PEG-12 polydimethylsiloxane interface-modified latex particle dispersion system. In step A7, the preservation component is added to the dispersion system obtained in step A6 and the pH value is adjusted. After stirring and filtration, the preservation-type waterborne MQ organosilicon film-forming resin is obtained. At the end of step A5, the retention rate of PEG-12 polydimethylsiloxane in the trimethylsiloxysilicate-PEG-12 polydimethylsiloxane interface-modified latex particles is 60.00–95.00%, and the D50 of the trimethylsiloxysilicate-PEG-12 polydimethylsiloxane interface-modified latex particles is 80–500 nm, and the PDI is 0.08–0.
35. The preservation-type waterborne MQ organosilicon film-forming resin has a solid content of 32.00–58.00 wt% and a pH value of 5.50–7.
50.
7. The aqueous MQ organosilicon film-forming resin according to claim 6, characterized in that, Steps A2 to A7 must satisfy the following process parameters: In step A2, 100 parts by weight of the trimethylsiloxysilicate is mixed with 8–30 parts by weight of ethanol and 0–10 parts by weight of deionized water, and stirred at 45–70°C for 0.50–2.00 h. In step A3, the amount of PEG-12 polydimethylsiloxane added is 4–20 parts by weight, the mixture is stirred at 50–75°C for 0.50–3.00 h, and the pH of the system is adjusted to 5.50–7.
50. In step A4, the shearing conditions are 1500–8000 rpm, the amount of deionized water added is 80–180 parts by mass, and the addition time is 0.50–3.00 h; In step A5, the aging treatment temperature is 30–60℃ and the time is 1.00–6.00h; In step A7, 0.20–1.50 parts by mass of the preservation component are added to 100 parts by mass of the dispersion system obtained in step A6, and the pH value of the system is adjusted to 5.50–7.
50. The pH-adjusted system is stirred at 20–40°C for 0.50–2.00 h and filtered to obtain the preservation-type waterborne MQ organosilicon film-forming resin. The amounts of ethanol, deionized water, PEG-12 polydimethylsiloxane, pH adjustment component and preservation component added in steps A2 to A7 are coordinated to ensure that the obtained preservation-type waterborne MQ organosilicon film-forming resin meets the content range of each component.
8. A method for preparing the aqueous MQ organosilicon film-forming resin according to claim 1 or 2, characterized in that, Includes the following steps: S1. Provides trimethylsiloxysilicate, PEG-12 polydimethylsiloxane, deionized water and ethanol; S2. The trimethylsiloxysilicate is mixed with the ethanol and / or deionized water and heated and stirred to obtain a trimethylsiloxysilicate predispersant; S3. Add the PEG-12 polydimethylsiloxane to the trimethylsiloxysilicate predispersant and heat and stir to obtain an interfacial precomposite system; S4. Under shear conditions, the deionized water is added to the interfacial precomposite system to form a trimethylsiloxysilicate-PEG-12 polydimethylsiloxane interfacial modified latex particle dispersion; S5. The trimethylsiloxysilicate-PEG-12 polydimethylsiloxane interface-modified latex particle dispersion obtained in step S4 is subjected to aging treatment, and the pH value is adjusted to 5.50–7.
50. After filtration, water-based MQ organosilicon film-forming resin is obtained.
9. The preparation method according to claim 8, characterized in that, Steps S1 to S5 were repeated for 3 batches. The solid content of the obtained waterborne MQ organosilicon film-forming resin had an inter-batch coefficient of variation of 0.50–5.00%, and the D50 of the trimethylsiloxysilicate-PEG-12 polydimethylsiloxane interface-modified latex particles had an inter-batch coefficient of variation of 0.50–10.00%.
10. The application of an aqueous MQ organosilicon film-forming resin as described in any one of claims 1 to 7 in color cosmetics, characterized in that, The aqueous MQ silicone film-forming resin is added to a water-based cosmetic matrix to prepare foundation, lip makeup, eye makeup, or waterproof and long-lasting makeup products; wherein the content of the aqueous MQ silicone film-forming resin in the system after addition is 3.00–35.00 wt%, and the pH value of the makeup matrix is 5.50–8.00.
Citation Information
Patent Citations
Personal care composition containing polysiloxane reinforced silicone elastomer emulsions
CN101244018A
Aqueous methyl MQ silicone resin emulsion and preparation method thereof
CN109021574A
